2018
DOI: 10.1038/s12276-018-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TFF3 is involved in prostate carcinogenesis via blocking mitochondria-mediated apoptosis

Abstract: The overexpression of trefoil factor family 3 (TFF3) is observed in a variety of cancers, including prostate cancer (PCa), and its potential role in carcinogenesis, such as activating the PI3K/AKT pathway, is suggested. However, its role and its related mechanisms in prostate tumorigenesis remain unknown. To elucidate the role of TFF3 overexpression in PCa, we silenced TFF3 in two PCa cell lines that overexpressed TFF3 and explored the molecular mechanism behind its antiapoptotic role. We also examined TFF3 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…TFF3 silencing induces the mitochondria-mediated apoptosis signaling pathway by enhancing BAX translocating to the mitochondria and by increasing the expression of the mitochondrial pro-apoptotic proteins. Thus, it is useful to develop mitochondrial biomarkers related to carcinogenesis [ 31 ]. In addition, as important intracellular organelles, the mitochondria play a critical role in regulating cancer signaling pathway, by structural derangement and metabolic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…TFF3 silencing induces the mitochondria-mediated apoptosis signaling pathway by enhancing BAX translocating to the mitochondria and by increasing the expression of the mitochondrial pro-apoptotic proteins. Thus, it is useful to develop mitochondrial biomarkers related to carcinogenesis [ 31 ]. In addition, as important intracellular organelles, the mitochondria play a critical role in regulating cancer signaling pathway, by structural derangement and metabolic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that TFF3 overexpression markedly decreased the proliferation of the SW837 and LoVo CCC lines (49). TFF3 has also been reported to promote the migration and invasiveness of rat fibroblasts (50), the migration of gastric mucosal epithelial cells (51), and the proliferation, viability and survival of breast cancer (17) and prostate carcinoma cells (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the role of lncRNAs in PTC would be of great help to understand the occurrence and progression of PTC. ENST00000489676 is one of the transcripts of TFF3, which is a member of the trefoil family and plays an important role in the formation and progressing of some cancer types 21-23.In the present study, we aimed to explore the expression level and the role of ENST00000489676 in the pathogenesis of PTC.…”
Section: Introductionmentioning
confidence: 99%